How does dollarization affect real volatility and country risk? - Carrera, Jorge Eduardo (2000)
This study gives a non-traditional framework for the evaluation of the convenience of an asymmetric monetary association (such as dollarization), from the point of view of the country that gives up its monetary sovereignty. In the analytical part we discuss the relationship between nominal volatility, real volatility and country risk. Given the social loss function of the policymaker, we determine the necessary conditions for dollarization to improve social welfare. With this in mind, we concentrate in the analysis of two main aspects: 1) the degree of synchronization existing between the cycle of the leader and associated country, and 2) the effect and relative importance of the different channels (the trade and financial channels) that transmit the shocks from the central country (the United States). In the empirical part we perform an application of our analytical framework to the case of Argentina. To estimate the synchronization of the business cycles we use the coefficient of cyclical correlation, calculated for four different methodologies of de-trending. The effect and relative importance of the financial channel and the trade channel were extracted from the impulse-response functions and variance decompositions of a Vector Error Correction Model (VECM). We analyze the stability of the results altering the order of the variables, re-estimating the model with rolling sub-samples and modifying the deterministic component in the error correction mechanism. As a general result dollarization in Argentina would not only reduce the risk of devaluation but also reduce the real volatility of the economy and so the country risk. For that reason, from the financial point of view the advantages of dollarization will depend on how much society values the alternative of keeping open the possibility of adjusting to extraordinary shocks with the exchange rate parity